Диференційований підхід до лікування неалкогольної жирової хвороби печінки у хворих на цукровий діабет 2-го типу - Кравчун, Н. О.; Земляніцина, О. В.; Дорош, О. Г.; Чернявська, І. В. (Clinical Endocrinology and Endocrine Surgery, 2013)
The results of treatment of non-alcoholic fatty liver disease in patients with type 2 diabetes were performed in this work. The estimation of influence of different groups of medicinal preparations (alpha-lipoic acid, L-ornithine-L- aspartate, essential phospholipids, thiotriazolineand ademetionin) is given on the indexes of carbohydrate, lipid, protein metabolism and liver function. The differentiated positive influence of the indicate groups of medicinal preparations on metabolic indexes and indexes of the functional state of liver was shown.